Effect of different fertility levels and biofertilizers on quality and economics of knol-khol (Brassica oleracea var. caulorapa L.) under agroclimatic condition of Bikaner region (Current Horticulture, 2024)
A field experiment was conducted to find out the effect of fertility levels and biofertilizers on quality and economics of knoll-knol (Brassica oleracea var. caulorapa L.) at Horticulture Farm, College of Agriculture, Bikaner, during 2010-11. The experiment consisting of 16 treatments, viz. four levels of fertility and four different biofertilizer inoculations alone and in combination was laid out in RBD with three replications. The treatment combination, 100 per cent recommended dose of NPK + PSB, exhibited dry matter, protein, N and K content and uptake significantly higher over the control, than application of fertilizers and biofertilizers alone. It was statistically at par with 150 per cent recommended dose of NPK in combination with other biofertilizers inoculations. The maximum net return of ` 85,089/ha with the best of B:C ratio of 3.86 : 1 was obtained when its crop was treated with treatment combination of 100 per cent recommended dose of NPK + PSB.
Keywords: NPK; PSB; Quality; Economics; Biofertilizers; Inoculants; Net returns; Dose